Exploring health demographics of female collegiate rowers - Walsh, M.; Crowell, N.; Merenstein, D. (Journal of Athletic Training, 2020)
Context: Limited information exists about health patterns among female rowers at the collegiate level. Furthermore, the element of weight class (lightweights classified as <130 lb [59 kg]) as a factor in the physical and mental health of female collegiate athletes has not been investigated, despite weight requirements in sport being a risk factor for the female athlete triad. Objective: To test the hypotheses that (1) components of the female athlete triad were more prevalent in lightweight than in openweight rowers; (2) perceived stress levels were greater in lightweight than in openweight rowers; and (3) rowers who were unable to row due to injury had greater perceived stress levels than uninjured athletes. Design: Cross-sectional study. Setting: Twelve collegiate women's rowing programs consisting of 6 National Collegiate Athletic Association Division I openweight and 6 Intercollegiate Rowing Association-level lightweight teams. Patients or Other Participants: A total of 158 female collegiate rowers (78 lightweight, 80 openweight). Main Outcome Measure(s): An electronic survey addressing injury history, diet and eating habits and body image (according to the triad screening questionnaire), stress levels (Perceived Stress Scale), and athlete identity (Athlete Identity Measurement Scale) was administered. Results: Lightweight rowers reported limiting or carefully controlling foods more frequently than openweight rowers (41.9% to 29.9%, P = .013). A history of an eating disorder was more prevalent among lightweight than openweight rowers (25.7% to 13.0%, P = .048). Prevalences of stress fractures and menstrual irregularities did not differ between weight classes. Lightweight and openweight rowers' scores on the Perceived Stress Scale (16.0 ± 9.9 and 17.3 ± 6.4, respectively) were not different. Injured rowers scored higher on the Perceived Stress Scale (19.4 ± 7.2) than did uninjured rowers (16.6 ± 5.72). Conclusions: Weight class did not contribute to differences in the prevalence of female athlete triad components or perceived stress, although lightweight rowers were more likely to have a history of eating disorder. Injury may be a risk factor for increased stress in this population.